AGE OF THE SHANUCH COPPER-NICKEL DEPOSIT IN KAMCHATKA - Stepanov V.A.; Trukhin Yu.P. (My University, 2007)
Copper–nickel deposits associated with hornblende-rich basic or norite–cortlandite minor intrusions and dikes are widespread at the eastern margin of the Asian continent. They are generally confined to carbonaceous metaschists or gneisses of median crystalline massifs or swells in the Precambrian basement of fold belts. The age of the copper–nickel mineralization in this region ranges from Proterozoic to Late Cretaceous.
Keywords: Cenozoic::Paleogene::Eocene; Кайнозой::Палеоген::Эоцен